Pengembangan Media Pembelajaran Audio Visual menggunakan Model Pembelajaran Discovery Learning untuk Meningkatkan Kemampuan Menulis Teks Berita pada Siswa Kelas XI SMK - Abdullatip Munawar; Teti Sobari; Heri Isnaini (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2026)
This research aims to develop audio-visual learning media based on the Discovery Learning model to improve the ability to write news texts in grade XI students of SMK Mutiara Qolbu Cianjur. The Research and Development (R&D) method is used by referring to the development model which includes the stages of identification of potentials and problems, data collection, product development, product validation, limited scale trials, product revisions, large-scale trials, final revisions, and final products. The research subjects consisted of 103 students in grade XI of SMK Mutiara Qolbu Cianjur which were divided into three classes. Data collection techniques were carried out through observation, interviews, questionnaires, expert validation, and news text writing tests. Data were analyzed using quantitative and qualitative descriptive techniques. The results of the study show that audio-visual learning media based on the Discovery Learning model obtained a very good feasibility level based on the results of the validation of material experts with a percentage of 91% and the validation of media experts of 89%. The results of the trial showed that the learning media received a positive response from students with an average percentage of 87.25%. In addition, the use of Discovery Learning-based audio-visual learning media has proven to be effective in improving students' ability to write news texts. This is shown by the increase in the average score of students from 64.21 in the pre-test to 84.37 in the post-test. The use of audio-visual media also improves students' learning activities, such as active questioning, discussion participation, and the ability to identify news elements.